Regular three-dimensional presentations improve in the identification of surgical liver anatomy: a randomized study - Müller, Beat P.; Löb, Nicole; Wald, Diana; Bruckner, Thomas; Meinzer, Hans-Peter; Kadmon, Martina; Büchler, Markus W.; Fischer, Lars (BMC medical education, 2013)
Three-dimensional (3D) presentations enhance the understanding of complex anatomical structures. However, it has been shown that two dimensional (2D) “key views” of anatomical structures may suffice in order to improve spatial understanding. The impact of real 3D images (3Dr) visible only with 3D glasses has not been examined yet. Contrary to 3Dr, regular 3D images apply techniques such as shadows and different grades of transparency to create the impression of 3D.
Gesehen am 29.06.2021